Other quotations of instrumentation and monitoring work by the third party - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the other quotations of instrumentation and monitoring work by the third party of Brac University new campus development project .